2006
DOI: 10.1016/j.neuron.2006.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Hyperekplexia Phenotype of Glycine Receptor α1 Subunit Mutant Mice Identifies Zn2+ as an Essential Endogenous Modulator of Glycinergic Neurotransmission

Abstract: Zn(2+) is thought to modulate neurotransmission by affecting currents mediated by ligand-gated ion channels and transmitter reuptake by Na(+)-dependent transporter systems. Here, we examined the in vivo relevance of Zn(2+) neuromodulation by producing knockin mice carrying the mutation D80A in the glycine receptor (GlyR) alpha1 subunit gene (Glra1). This substitution selectively eliminates the potentiating effect of Zn(2+) on GlyR currents. Mice homozygous for Glra1(D80A) develop a severe neuromotor phenotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 44 publications
9
105
0
Order By: Relevance
“…10). As expected, we found that Zn 2ϩ sensitivity of wild-type transport was pH-dependent, being higher at pH 7.4 than 5.4, in agreement with the competitive nature of H ϩ and Zn 2ϩ inhibition (35,38,39). By contrast, the inhibition by Zn 2ϩ of the Y705C mutant was much less sensitive to the presence of protons and slightly more pronounced at acidic pH.…”
Section: Y705c Mutant Is Partially Resistant To Zn 2ϩsupporting
confidence: 88%
“…10). As expected, we found that Zn 2ϩ sensitivity of wild-type transport was pH-dependent, being higher at pH 7.4 than 5.4, in agreement with the competitive nature of H ϩ and Zn 2ϩ inhibition (35,38,39). By contrast, the inhibition by Zn 2ϩ of the Y705C mutant was much less sensitive to the presence of protons and slightly more pronounced at acidic pH.…”
Section: Y705c Mutant Is Partially Resistant To Zn 2ϩsupporting
confidence: 88%
“…Release of endogenous Zn 2ϩ in CNS tissue is estimated to raise extracellular Zn 2ϩ concentrations to levels of Ϸ10 M (31). Because 10 M Zn 2ϩ results in a pronounced potentiation of the glycine-induced currents of NR1/NR3A receptors and low micromolar concentrations of this metal ion have been shown to be essential for proper functioning of the inhibitory glycine receptor in vivo (32), the Zn 2ϩ potentiation of NR1/NR3A receptor currents disclosed here may be of physiological importance in vivo. Alternatively, the NR1/NR3A receptor modulation, activation, and supralinear potentiation reactions depicted in Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Positive clones were identified by PCR and confirmed by Southern blot analysis using external and internal probes. Two targeted ES clones were expanded for Cre-mediated deletion in ES cells by transient transfection with a Cre recombinase expression vector as described previously (Hirzel et al, 2006). Neo excision was confirmed by PCR and Southern blotting.…”
Section: Methodsmentioning
confidence: 99%